1991
DOI: 10.1042/cs0810327
|View full text |Cite
|
Sign up to set email alerts
|

Altered small-intestinal permeability associated with diarrhoea in human-immunodeficiency-virus-infected Caucasian and African subjects

Abstract: 1. Small-intestine integrity in Caucasian and African patients infected with human immunodeficiency virus was determined by measuring the permeation across the mucosa of two sugars, lactulose and mannitol. 2. The sugars were assayed by h.p.l.c. and pulsed amperometric detection in 6 h urine samples. Stool microscopy for enteropathogens was performed in all patients. 3. The ratio of lactulose to mannitol recovered in urine was increased in Caucasian and African patients with advanced human immunodeficiency viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…Importantly, of the permeability studies, none found any evidence of enteropathy in early HIV. 9,34,35,41 Taken together, although there are some enteropathic changes (crypt hyperplasia, cytokine dysregulation) in early HIV infection, the most important changes from the perspective of MT are predominantly seen in advanced disease.…”
Section: Enteropathy Is a Feature Of Hiv Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, of the permeability studies, none found any evidence of enteropathy in early HIV. 9,34,35,41 Taken together, although there are some enteropathic changes (crypt hyperplasia, cytokine dysregulation) in early HIV infection, the most important changes from the perspective of MT are predominantly seen in advanced disease.…”
Section: Enteropathy Is a Feature Of Hiv Infectionmentioning
confidence: 99%
“…33 Individuals with advanced disease developed a chronic, inflammatory enteropathy, frequently characterized by malabsorption and increased intestinal permeability. 34,35 However, before late-stage AIDS most HIV-infected individuals had fairly normal gut structure and function. 34,35 More recently, attention has refocused on the impact of HIV on the gut, following the observation that damage to the intestine may modulate HIV disease progression even before symptomatic gastrointestinal disease.…”
Section: Enteropathy Is a Feature Of Hiv Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] Histologically, the enteropathy involves inflammatory infiltrates of lymphocytes and damage to the GI epithelial layer, including villous atrophy, crypt hyperlasia, and villous blunting. [7][8][9] Importantly, these pathologic changes occur in the absence of the detectable bacterial, viral, or fungal enteropathogens that are often associated with enteropathy.…”
mentioning
confidence: 99%